Potential socio-economic challenges facing small-scale sugarcane production in Bungoma County, Kenya - Khaemba, Protas Fwamba; Muiruri, Philomena W. (Research Journal in Advanced Social Sciences, 2022)
The sugar industry is an important agricultural sector in Kenya. In 1995, the industry had employed over 35,000 workers and supported over 2 million people in the region. The sector contributes about 16% to the nation’s Gross Domestic Product. Despite of its immense contribution, its output is on decline, standing at 65 tonnes from 100 tonnes per hectare. This paper investigated socio-economic factors affecting sugarcane production in Bungoma County. The study is based on the Production Theory and Correlation Design. The targeted population was 5,838 small scale sugarcane farmers in Bumula Sub-County. The coefficient of determination indicated 67.5% variance in sugarcane output relating to the socio-economic factors of the study variables. The F value was 161.406 indicating that the regression model was fitting well. The mean variance of inflation factor (VIF) was 2.349. The study revealed that education level, farm size, land ownership, farming experience, incentives, record keeping systems, extension education, cane by-products and non-contracted cane farming had significant positive effect on cane output. Input cost was found to be a major contributor of declining cane output. The study recommends that poor cane pricing, lack of extension education and inadequate financing in the sugar sector be addressed.